Seizure prophylaxis following aneurysmal subarachnoid haemorrhage (SPSAH): study protocol for a multicentre randomised placebo-controlled trial of short-term sodium valproate prophylaxis in patients with acute subarachnoid haemorrhage. Issue 5 (4th May 2022) - Chen, Yuqi; Fang, Mei; Wu, Pei; Xie, Zhiyi; Wu, Honggang; Wu, Qiaowei; Xu, Shancai; Li, Yuchen; Sun, Bowen; Pang, Bo; Zheng, Niandong; Zhang, Jianmin; et al.
Abstract : Introduction: Seizures are a common complication that leads to neurological deficits and affects outcomes after aneurysmal subarachnoid haemorrhage (aSAH). However, whether to use prophylactic anticonvulsants in patients with aSAH remains controversial. Our study aims to determine whether short-term (7 days) sodium valproate could prevent seizure occurrence and improve neurological function in patients with SAH caused by anterior circulation aneurysm rupture and treated with clipping. Methods and analysis: In this multicentre randomised evaluator-blind placebo-controlled trial, 182 eligible patients with good-grade aSAH planned for surgical clipping will be enrolled from four neurosurgical centres in China. In addition to standard care, patients will be randomly assigned to receive sodium valproate 20 mg/kg daily or matching placebo. After aneurysmal clipping, patients will be followed up at discharge, 90 days and 180 days. The primary outcomes are the incidence of early and late seizures. The secondary outcomes include aSAH-related complications, sodium valproate-related adverse effects, modified Rankin Scale (mRS) (on discharge, at 90 days, 180 days), rate of good outcome (defined as mRS 0–2), all-cause death (at 90 days, 180 days) and Montreal Cognitive Assessment score (at 180 days). All analyses are by intention-to-treat. Ethics and dissemination: This study will be conducted according to the principles of Declaration of Helsinki and good clinical practice guidelines. This trial involves human participants and has been approved by the ethics committee of West China Hospital. Informed consent will be achieved from each included patient and/or their legally authorised representative. Preliminary and final results from this study will be disseminated through manuscript publishing and international congresses presentations. Any protocol amendments will be approved by the ethics committee of West China Hospital and subsequently updated on ChiCTR. Trial registration number: ChiCTR.org identifier: ChiCTR2100050161.